(untitled) (Research, Society and Development, 2022)
The objective will be to map the available scientific literature on brain structural changes and/or damage in frail older adults. Literature published in English, Portuguese or Spanish will be searched in PubMed, PubMed PMC, BVS – BIREME, Embase, SCOPUS, Cochrane, Web of Science, Proquest, PsycInfo EBSCOHOST and Ageline databases. Two authors will review the title, abstract and full texts for eligibility. The PRISMA recommendations will be used to extract data from the reviewed studies, according to the following criteria: studies involving frail older adults (age ≥ 60 years); literature reporting structural and functional brain changes in neuroimaging exams; studies carried out in clinics and in the community; primary studies; studies published in English, Portuguese, or Spanish. The extracted data will be tabulated, along with a narrative summary.